If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 46x + 1 + 42 = 1 + 68x Reorder the terms: 1 + 42 + 46x = 1 + 68x Combine like terms: 1 + 42 = 43 43 + 46x = 1 + 68x Solving 43 + 46x = 1 + 68x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-68x' to each side of the equation. 43 + 46x + -68x = 1 + 68x + -68x Combine like terms: 46x + -68x = -22x 43 + -22x = 1 + 68x + -68x Combine like terms: 68x + -68x = 0 43 + -22x = 1 + 0 43 + -22x = 1 Add '-43' to each side of the equation. 43 + -43 + -22x = 1 + -43 Combine like terms: 43 + -43 = 0 0 + -22x = 1 + -43 -22x = 1 + -43 Combine like terms: 1 + -43 = -42 -22x = -42 Divide each side by '-22'. x = 1.909090909 Simplifying x = 1.909090909
| 27x(3-2c)=15 | | 5(3x+6)=-23+38 | | 13-x=x^2-2x+1 | | y=2y-11 | | 2.45-3.1t= | | 5x-8x+12=35-6x | | 3x+28=7x+44 | | Y^3-4y^2-45y=0 | | 6v-2+5=-21 | | 2x^2+17x-9.3=0 | | 12(x+2)=48 | | 12x+6y+4x+9y= | | 14a^4-23a^2+8=0 | | -5=-50 | | 5k+2k=28 | | 8x+3=2(4x+5) | | 10-14x=38+0x | | 6n+10=2(4n+5)-2n | | 17n+2= | | 4(t+7)=-3t+7 | | 2x+3(5-x)=25 | | -4(t-2)+7t=8t-2 | | 8-w^3= | | 15-4x=5x-25 | | -3+2y=7y+12 | | 7(x+3)-6x=-18 | | -2+8x=18 | | 21x-3x=9 | | 4y+6y-2y= | | 14x+5+130=59x | | 17x-6=00 | | X+6=12+x |